Development and regional expression of beta nerve growth factor messenger RNA and protein in the rat central nervous system. - Whittemore, S R (1986)
The presence of nerve growth factor (NGF) mRNA and protein in the rat central nervous system is documented. Blot-hybridization analysis showed an abundance of NGF mRNA in the hippocampus, cerebral cortex, and olfactory bulb. Enzyme immunoassay confirmed significant levels of a NGF-like protein in the hippocampus and cerebral cortex. Bioassay of a NGF-like immunoaffinity-purified protein from these regions was physiologically indistinguishable from NGF. Immunohistochemistry revealed a widespread distribution of NGF-like reactivity in the adult brain, preferentially in fiber tracts. NGF mRNA accumulation began at birth, with adult levels reached 3 weeks postnatally. Enzyme immunoassay detected the presence of a NGF-like protein in the embryonic rat brain. Postnatally, the level of NGF-like protein reached a maximum at 3 weeks. Additionally, a distinct fetal form of NGF may exist.